KAJIAN LITERATUR BERBASIS FAKTA DAN DAMPAK ROTASI INTI BUMI TERHADAP MAKHLUK HIDUP - Rieke Nur Fitria; Hanin Nabila; Qurrotul A’yunin Nafi’ah; An Nuril Maulida Fauziah (Jurnal Reflektif, 2026)
Basically, the solar system has planets, one of which is the earth, which has an inner layer in the form of the earth's core. In the earth's core, the rotation of the earth's core can occur. This article aims to identify the mechanism of the causes and movements of the earth's core rotation, the facts and possibilities that occur in the rotation of the earth's core, and the impacts caused for the survival of living things in the future. This article uses the Literature Review method in discussing this article from various national and international journals which are then processed and summarized. This article discusses the rotation of the earth's core which is the movement of the core on the earth that rotates on its axis with the direction of rotation counterclockwise. At the core of the earth there is a liquid outer core and a solid inner core whose temperature is up to 4,300-6000 K. Electromagnetic torque originating from the result of the magnetic field in the outer core and gravity between the inner core and mantle that affects the rotational movement of the earth's core. Research shows that currently the rotation of the earth's core undergoes cyclical changes for 60-70 years and affects the earth's magnetic field. The rotation of the earth's core that affects the earth's magnetic field also affects the protection of the planet from solar cosmic radiation, navigation of migratory animals, and natural disaster phenomena that occur on earth. This makes the earth has complex dynamics because of the phenomena that occur.